Enhancing Student Learning in Middle School. - Casas, Martha (Taylor & Francis, 2010)
Offering an introduction to middle school teaching, this title focuses on the instructional strategies that encourage adolescents to become active participants in their own learning within a world of accountability and standardized testing. It follows a constructivist approach to teaching that considers the whole child.